LEXICAL ANALYSIS OF THE LANGUAGE EMERGENCE IN BAGAC, BATAAN: BASIS FOR LOCAL LANGUAGE DICTIONARY - B. Monis, Rupert John (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This research delves into the intricate processes of language emergence, particularly focusing on lexical analysis, in the unique context of Bagac, Bataan, Philippines. Bybee's insights into lexical item evolution and Croft's evolutionary approach to language change contribute significantly to understanding the principles shaping language emergence. The study encompasses various subfields like morphology, etymology, and semantics, offering a holistic perspective on how languages develop. Employing a sequential-explanatory design, the research combines cross-sectional and longitudinal elements. Explanatory research complements the study, unraveling details in areas with limited information, which is vital for exploring language emergence. The population comprises residents from four barangays in Bagac, Bataan, utilizing a stratified-random sample. Furthermore, for Phase 1, a self-made survey questionnaire gauges respondents' profiles, language usage, and attitudes. Phase 2 employs purposive sampling for in-depth interviews with four participants, emphasizing the saturation point in data collection to ensure thorough exploration. Aside from this, research instruments include a survey questionnaire for quantitative data in Phase 1, probing into demographics, language usage, and attitudes. For Phase 2, a semi-structured interview, observation, and verbal elicitation through discourse provide rich qualitative data. Verbatim transcription captures participants' exact words, subsequently analyzed through Thematic Analysis. Moreover, research contributes a multifaceted exploration of language emergence, employing a robust methodology that combines quantitative and qualitative approaches. By focusing on Bagac, Bataan, the study adds valuable insights to the broader understanding of how languages develop and adapt in unique sociolinguistic contexts.